Synthesis of priorities for the AgriLAC Resiliente One CGIAR Regional Integrated Initiative - Ramírez Villegas, Julián Armando; Slavchevska, Vanya; Meentzen, Angela; Paez-Valencia, Ana María; Castro-Nuñez, Augusto Carlos; Martínez Barón, Deissy (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This info note summarizes the key challenges addressed by the regional initiative ''AgriLAC Resiliente'', onto the One CGIAR impact areas; across all relevant countries in the region. Across all impact areas, are synthesize a set of country-level priorities that will form an initial list of priority geographies.